PENGARUH SPESIALISASI AUDITOR DAN AUDIT TENURE TERHADAP KUALITAS AUDIT - EKA YUNIAR MAHARANI, DESTIAN; NYOMAN ALIT TRIANI, NI (Jurnal Akuntansi AKUNESA, 2019)
The low audit quality issues are things that need to be considered because they are unable to preparing an accurate audit report. This can happen to all Public Accounting Firm, including Public Accounting Firm that have high credibility, the Big Four. Evidenced by the existence of several phenomena case of low audit quality produced by Public Accounting Firm wich is included in Big Four, which was reported from the latest PCAOB announcement (Public Company Accounting Oversight Board) in 2016 and 2017 regarding sanctions given to several Big Four of Public Accounting Firm. This makes need for research to determine the effect of auditor specialization and audit tenure on audit quality in manufacturing companies audited by the Big Four of Public Accounting Firm. Purposive sampling is used to determine the sample in this study, so that is obtained 49 companies. The data analysis technique used in this study is multiple regression analysis with the SPSS 23 test tool and results are the audit tenure affects on audit quality, while auditor specialization does not affect audit quality.